Stability of mandibular advancement with the use of mandibular thrusters: A literature review - Arredondo Capa , José Angel (2025)
The purpose of this review was to gather recent information on the stability of mandibular advancement using mandibular advancement devices. To achieve this, studies published between 2018 and 2024 were reviewed, retrieved from search engines such as PubMed, Scopus, Cochrane, Pesquisa, Taylor & Francis, and Google Scholar. The results indicate that mandibular advancement devices are effective in improving the intermaxillary relationship, correcting dental occlusion, and aligning the mandible in patients with Class II malocclusion. These devices also help alleviate the symptoms of obstructive sleep apnea by facilitating airflow through the upper airways. Additionally, some appliances help relieve tension in the masticatory muscles and can improve facial aesthetics by correcting the mandibular position. Among the most commonly used appliances to achieve mandibular advancement are the Herbst appliance, the mandibular advancement appliance, and the anterior mandibular repositioning appliance. To ensure long-term treatment effectiveness, proper appliance adjustment and regular follow-up are essential. In conclusion, although mandibular advancement devices offer significant benefits, their long-term stability depends on proper patient adaptation, consistent monitoring, and precise appliance adjustment. Studies suggest that continuous supervision is crucial to avoid complications and ensure treatment effectiveness over time.